Developing Luwu Folktales Bilingual Book (English and Tae Language) As Reading Material For 10th Grade of Man Palopo - Atina Yoso Negara, Artadinah; Rustan Santaria; Madehang; Ermawati; Dewi Furwana (Indonesian TESOL Journal, 2025)
This study aims to develop a Luwu folktales book that can help students of 10th grade at MAN Palopo and to determine students perception of Luwu folktales book. The method used in this research is Research and Development (R&D) with the 4D model, which consists of four stages: Define, Design, Develop, and Disseminate. The research instruments used was interviews and questionnaire. The outcome of the study is: 1). Luwu Folktales book consisting of 7 units, namely Princess Tandampalik, The Story of King Luwu, The Legend of Sawerigading, The Legend of To Manurung, History if Bulu Poloe, Mount Bambapuang, Batu Mebali Village. 2). Students' perceptions of the Luwu folktales book are very positive with a score of 4.3, the average percentage value reaching 86%. Based on the results of expert validation, the design and layout validation score was 90% with a ‘very good’ category, language validation score was 84% with a ‘very good’ category and material validation score was 80% with a ‘good’ category. and also the results of teacher' perceptions obtained a “good” category. Therefore, the Luwu folktales book for 10th grade students is suitable as a medium for reading material  for 10th grade students and students in general.